2019
DOI: 10.1021/acs.macromol.9b00521
|View full text |Cite
|
Sign up to set email alerts
|

Ester-Functionalized Naphthobispyrazine as an Acceptor Building Unit for Semiconducting Polymers: Synthesis, Properties, and Photovoltaic Performance

Abstract: Strongly electron-deficient π-conjugated systems are key building units for semiconducting polymers that are used in organic electronic devices, such as organic photovoltaic (OPV) cells. Here, we designed and synthesized a naphthobispyrazine derivative bearing four ester groups (eNPz) as a new electron-deficient building unit and three eNPz-based semiconducting polymers with different donor units, that is, bithiophene (PeNPz2T), terthiophene (PeNPz3T), and quaterthiophene (PeNPz4T). These new polymers have rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Due to their excellent properties such as optoelectronic designability, low-cost solution processability, and polymeric flexibility, semiconducting polymers have been extensively researched for many applications in OFETs, , printable integrated circuits, , wearable ultralight sensors, , large-area photovoltaic devices, ,, etc. For example, it was demonstrated that semiconducting conjugate polymer-based solar cells can reach high power conversion efficiencies (PCEs), around 6%. However, the low charge carrier mobilities for semiconducting polymers still restrict their practical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their excellent properties such as optoelectronic designability, low-cost solution processability, and polymeric flexibility, semiconducting polymers have been extensively researched for many applications in OFETs, , printable integrated circuits, , wearable ultralight sensors, , large-area photovoltaic devices, ,, etc. For example, it was demonstrated that semiconducting conjugate polymer-based solar cells can reach high power conversion efficiencies (PCEs), around 6%. However, the low charge carrier mobilities for semiconducting polymers still restrict their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…For example, its excellent properties and the single atomic thickness are advantageous for use in many organic electronic devices such as organic field-effect transistors (OFETs), 12,13 organic light-emitting diodes (OLEDs), 14,15 and organic photovoltaics (OPVs). 16 Due to their excellent properties such as optoelectronic designability, low-cost solution processability, and polymeric flexibility, semiconducting polymers have been extensively researched for many applications in OFETs, 17,18 printable integrated circuits, 19,20 wearable ultralight sensors, 21,22 largearea photovoltaic devices, 20,23,24 etc. For example, it was demonstrated that semiconducting conjugate polymer-based solar cells can reach high power conversion efficiencies (PCEs), around 6%.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We have recently reported a series of polymers based on dicyano NTz (CN-NTz), which also exhibits enhanced electron deficiency compared to NTz, and found that the polymers have ambipolar to n-type semiconducting characteristics depending on the co-monomer unit in the backbone . We have also focused on π-conjugated polymers based on naphtho­[1,2- b :5,6- b ′]­bispyrazine (NPz), which is an analogue of NXz (Figure a), , whereas other groups have reported NPz-based polymers as p-type semiconductors for OPVs. An important feature of NPz is that it allows the introduction of four substituents at 2-, 3-, 8-, and 9-positions, in contrast to NTz and NOz. For instance, alkyl, aromatic, and ester groups have been introduced at these positions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have been focusing on naphtho­[1,2- c :5,6- c ′]­bis­[1,2,5]­thiadiazole (NTz) and related heteroaromatic rings as relatively strong acceptor units for semiconducting polymers (Figure ). Owing to the large π-conjugated systems and the symmetry of the units, the polymers having these building units formed crystalline structures in the thin film and showed high charge carrier mobilities as high as 1 cm 2 V –1 s –1 . Further, these polymers had narrow band gaps because of the strong donor–acceptor intramolecular interactions, which contributed to their high photovoltaic properties.…”
Section: Introductionmentioning
confidence: 99%